PENGARUH PELAKSANAAN KEWENANGAN PENGHULU (DATUAK) MELALUI KERAPATAN ADAT NAGARI DALAM SISTEM PEMERINATAHAN DI KENAGARIAN SALIDO SARI BULAN KABUPATEN PESISIR SELATAN PROVINSI SUMATRA BARAT - Zindy Afreza; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The exercise of authority is a series of activities related to formal power or authority in order to achieve a certain goal, the authority of the Penghulu/Datuak in Kenagarian Salido Sari Bulan where this has an influence on the implementation of the authority itself. This problem was motivated by the existence of regional expansion in the South Coastal area of West Sumatra, namely the Kenagarian Mine which was expanded into 3 regions, namely Nagari Salido Sari Bulan, Nagari Kotorawang and Nagari Tambang because of that there was a massive restructuring where at this time there were no written regulations. regarding the authority of the penghulu in Nagari Salido Sari Bulan, where in the Nagari there are Penghulu/Datuak from 5 tribes namely Caniago, Malay, Tanjuang, Bendang and Jambak totaling 17 people.This study aims to see how the implementation of the authority of the Penghulu in Nagari Salido Sari Bulan after the division took place. The research approach used is a qualitative approach where this research was carried out in Kenagarian Salido Sari Bulan Pesisir Selatan Regency, West Sumatra Province and data collected through interviews and documentation based on problems.The results of this study are in the West Sumatra Regional Regulation number 7 of 2018 paragraph 14 it is said that Niniak Mamak is a person who is appointed as a traditional leader by a tribe or tribe, where Niniak Mamak is the main member of the Nagari Adat Density (KAN), KAN has the official authority to cooperate with the Nagari Government, the magnitude of the influence of the Penghulu in KAN causes some of the duties and authorities of KAN to be carried out by the Penghulu or Niniak Mamak as an important member of the KAN, so this affects the implementation of the authority exercised by the Penghulu in the Nagari Government System .   Keywords: Authority, Penghulu (Datuak), Nagari